2020
DOI: 10.2217/bmm-2020-0417
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Pleckstrin Homology-Like Domain, Family A Family Members in Breast Cancer

Abstract: Aim: The PHLDA (pleckstrin homology like domain, family A) gene family encodes proteins capable of inhibiting AKT (serine/threonine kinase) signaling through phosphoinositol binding competition. Results & methodology: Using in silico analysis, we found that Luminal A and B patients' short relapse-free survival was associated with low PHLDA1 or PHLDA3 and high PHLDA2 expression. In a cohort of 393 patients with luminal breast cancer evaluated by immunohistochemistry on tissue microarrays, we found a direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Whereas, the PI3K/AKT/mTOR signaling pathway has been consistently implicated in resistance to several therapies in breast cancer (31) and that proteins with the PH domain can bind to phosphatidylinositol coupled to the surface of the intracellular membrane for suppression of this important oncogenic signaling pathway (9), we can hypothesize that PHLDB1 and 3 appear to be promising molecules to stratify patients who may or may not respond to hormone therapy and anti-HER2 agents. In addition to our findings, other studies have already demonstrated a possible relationship between the members of the PHLD family for therapeutic response in cases of Luminal and HER2+ breast cancer (16,17,24,32).…”
Section: Variablessupporting
confidence: 84%
See 1 more Smart Citation
“…Whereas, the PI3K/AKT/mTOR signaling pathway has been consistently implicated in resistance to several therapies in breast cancer (31) and that proteins with the PH domain can bind to phosphatidylinositol coupled to the surface of the intracellular membrane for suppression of this important oncogenic signaling pathway (9), we can hypothesize that PHLDB1 and 3 appear to be promising molecules to stratify patients who may or may not respond to hormone therapy and anti-HER2 agents. In addition to our findings, other studies have already demonstrated a possible relationship between the members of the PHLD family for therapeutic response in cases of Luminal and HER2+ breast cancer (16,17,24,32).…”
Section: Variablessupporting
confidence: 84%
“…Considering the reports of some previous studies indicating PHLD family members as potential biomarkers for response to different treatments (16,17), we conducted an analysis with the ROC Plotter web tool. Our results showed that among patients with hormone-dependent tumors, those who did not respond to hormone treatment had significantly reduced expression of PHLDB1 in cases classified as Luminal A (p = 0.040) (Figure 5a), but there was no relationship in Luminal B tumors (p = 0.054) (Figure 5b).…”
Section: Predictive Value Of Phldb Family Members For Treatment Responsementioning
confidence: 99%
“…In recent years, people have paid increasing attention to the function of the PHLDA family members in tumors. Relevant studies have found that PHLDA family members have potential tumor suppressor or cancer-promoting roles in various malignancies, such as breast, rectal, and lung cancer [ 13 , 21 , 22 ]. However, functional studies of PHLDA family members in PAAD are currently lacking, and no specific bioinformatics analysis has been performed.…”
Section: Discussionmentioning
confidence: 99%
“…Mangone et al found that breast tumor samples showed higher levels of PHLDA2 transcripts ( p < 0.0001) than normal tissue samples. Besides, PHLDA2 could act as a prognostic marker and predict a response to endocrine therapy in BRCA ( R Mangone et al, 2020 ). Moon et al also concluded that the expression of PHLDA was high in triple negative BRCA cells ( Moon et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%